2007
DOI: 10.1086/512864
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Potocki-Lupski Syndrome (dup(17)(p11.2p11.2)) and Delineation of a Dosage-Sensitive Critical Interval That Can Convey an Autism Phenotype

Abstract: The duplication 17p11.2 syndrome, associated with dup(17)(p11.2p11.2), is a recently recognized syndrome of multiple congenital anomalies and mental retardation and is the first predicted reciprocal microduplication syndrome described--the homologous recombination reciprocal of the Smith-Magenis syndrome (SMS) microdeletion (del(17)(p11.2p11.2)). We previously described seven subjects with dup(17)(p11.2p11.2) and noted their relatively mild phenotype compared with that of individuals with SMS. Here, we molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
374
0
13

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 329 publications
(402 citation statements)
references
References 69 publications
(126 reference statements)
12
374
0
13
Order By: Relevance
“…26,27 While haploinsufficiency of RAI1 results in the majority of clinical features of SMS, its role in the reciprocal duplication 17p11.2 syndrome is not clearly understood. 4,5 Human chromosome 17 is syntenic to a approximately 34-cM region of mouse chromosome 11, in which 19 genes are conserved in order and orientation. 28,29 Mouse models for SMS and dup(17)(p11.2p11.2) syndromes, Df(11)17 þ and Dp(11)17 þ , heterozygous for either a deletion or a duplication, respectively, encompassing an approximately 3 Mb mouse syntenic region, have been created, while a gene targeting approach was used to create Rai1 þ /À mice (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26,27 While haploinsufficiency of RAI1 results in the majority of clinical features of SMS, its role in the reciprocal duplication 17p11.2 syndrome is not clearly understood. 4,5 Human chromosome 17 is syntenic to a approximately 34-cM region of mouse chromosome 11, in which 19 genes are conserved in order and orientation. 28,29 Mouse models for SMS and dup(17)(p11.2p11.2) syndromes, Df(11)17 þ and Dp(11)17 þ , heterozygous for either a deletion or a duplication, respectively, encompassing an approximately 3 Mb mouse syntenic region, have been created, while a gene targeting approach was used to create Rai1 þ /À mice (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Patients with dup(17)(p11.2) syndrome present with mental retardation, preand postnatal growth retardation, cognitive impairment, craniofacial abnormalities, heart defects, and hyperactivity. 1,5 More than 40 patients with dup(17)(p11.2p11.2), ranging from 1.3 to 15 Mb in size, have been described. 1,5 The critical region for the duplication has been narrowed down to approximately 1.3 Mb and also contains RAI1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Two more well-characterized examples are Williams syndrome (OMIM 194050), due to a microdeletion at 7q11.23, and its reciprocal microduplication syndrome (OMIM 609757); 18,19 and Smith-Magenis syndrome (OMIM 182290), due to microdeletion at 17p11.2, and Potocki-Lupski syndrome (OMIM 610883), caused by the reciprocal microduplication. 20,21 Analysis of the phenotypic consequences of the reciprocal NF1 microduplications, however, has been reported in detail in just one multigenerational family. Grisart et al 22 reported seven members of a multigeneration family segregating the 1.4-Mb reciprocal microduplication of the type 1 NF1 microdeletion.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Several clinically distinct microdeletion and microduplication syndromes have been reported on the basis of data derived from these techniques, such as the 17q21.31 microdeletion syndrome 5 and the 1q41-1q42 microdeletion syndrome, 9 as well as microduplication syndromes involving 7q11.23 10,11 and 17p11.2. 12 The phenotypic characteristics of microdeletion syndromes can be caused by haploinsufficiency of single genes, for example, TCF4 (MIM 602272) in Pitt-Hopkins syndrome, 13 EHMT1 (MIM 607001) in the 9q34.3 subtelomeric deletion syndrome 14 and either CREBBP (MIM 600140) or EP300 (MIM 602700) in Rubinstein-Taybi syndrome. 15,16 The application of genome-wide array technologies with an increasing density of probes has led to the identification and localization of several genes associated with developmental disorders or abnormal brain development, 8 including CHD7 (MIM 608892) in CHARGE syndrome 17 and FOXG1(MIM 164874) in congenital Rett syndrome.…”
Section: Introductionmentioning
confidence: 99%